THE DEVELOPMENT OF INTERNAL EDUCATION QUALITY ASSURANCE MODELS IN BAN PARA SCHOOL UNDER PHUKET PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Pairoj, Marisa; Jaroensuk, Natjaree; Mileman , Nanthapong (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1) were to investigate the status of the internal education quality assurance operating in the educational institution; 2) were to create and develop the internal education quality assurance model in the educational institution; and 3) were to assess the appropriateness and possibility of the internal education quality assurance model in the educational institution of Ban Para School under Phuket Primary Educational Service Area Office by using the model of the research and development consisted of 3 steps which were step 1: investigate the status of the internal education quality assurance in the educational institution. The population was 11 school administrators and teachers of Ban Para School. The research instrument was the questionnaire with a reliability index of 0.99; step 2: develop the internal education quality assurance model in the educational institution. The content validity was assessed by 5 experts, and step 3: assess the appropriateness and possibility of the model by 5 experts selected by the purposive sampling method. The research instrument was the assessment form of appropriateness and possibility. The collected data were analyzed by the basic statistics consisting of the percentage, mean, and standard deviation. The findings showed that 1) the overall status of the internal education quality assurance operating in Ban Para School under Phuket Primary Educational Service Area Office was at a high level; 2) the internal education quality assurance model of Ban Para School under Phuket Primary Educational Service Area Office was developed by using the PDCA cycle consisted of 3 steps which were (1) preparation and awareness-building, (2) operation, and (3) report; and 3) the overall appropriateness and possibility of the internal education quality assurance model in Ban Para School under Phuket Primary Educational Service Area Office was at the high level.